Hydrogels for Wound Dressing Applications - A Systematic Review - Memuna Kausar Satti, Sadaf Humayun, Muhammad Sajid, Kunza Naveed Asdaq, Tehreem Ashraf, Mahjabeen Aftab (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To discuss the currently available hydrogel wound dressings and their clinical effectiveness. Method: PubMed/Medline, HEC Digital Library, Wiley Online Library, Wolter Kluwer, Elsevier, and Google Scholar from the year 2013 to 2021 were searched to identify relevant clinical trials and studies. Results: Forty-three studies that assessed hydrogel vs. non-hydrogel dressings were identified. Compared to the latter, hydrogel dressings associated with a significantly shortened healing time of degree II burn (superficial and deep) wounds, diabetic foot ulcers, traumatic skin injuries, radioactive skin injuries, dog bites, and body surface ulcers. In addition, hydrogel dressing obviously increased the cure rate of diabetic foot ulcers, surgical wounds, dog bites, and body surface ulcers. Moreover, hydrogel dressing significantly relieved pain in degree II burn (superficial and deep) wounds, traumatic skin injuries and laser treatment-induced wounds. However, no significant differences obtained between hydrogel and non-hydrogel dressings in the healing time of surgical wounds, the cure rate of inpatients’ pressure ulcers, and phlebitis ulcers. Conclusion: This comprehensive systematic review of the available evidence reveals that the application of hydrogel dressings advances the healing of various wound types and effectively alleviates the pain with no severe adverse reactions. These results strongly indicate that hydrogel products are effective and safe in wound management. Keywords: Hydrogels, wound dressing, surgical wounds, diabetic ulcer, burns.